Effectiveness of Reading Comprehension Strategies in Improving the Reading Comprehension Performance of Grade 6 Pupils - Billao, Daisy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the effectiveness of reading comprehension strategies in improving the reading comprehension performance of Grade 6 pupils of Loo Elementary School. Reading comprehension is a critical literacy skill that influences learners’ academic success across subject areas, yet many elementary learners experience difficulty understanding texts, particularly at higher levels of comprehension. To address this concern, the study employed a quasi-experimental one-group pretest–posttest design. The participants were Grade 6 pupils enrolled during the school year 2024. A teacher-made reading comprehension test aligned with Grade 6 learning competencies was used to measure pupils’ comprehension performance in terms of literal, inferential, and evaluative comprehension. The intervention involved explicit instruction of reading comprehension strategies such as predicting, questioning, clarifying, summarizing, and the use of graphic organizers over several weeks. Results revealed an increase in pupils’ mean reading comprehension scores after the intervention across all comprehension levels. A paired-samples t-test indicated a statistically significant difference between the pretest and posttest results at the 0.05 level of significance. The findings suggest that explicit and systematic reading comprehension strategy instruction effectively enhances pupils’ ability to understand and analyze texts. The study concludes that integrating reading comprehension strategies into regular classroom instruction can significantly improve the reading comprehension performance of Grade 6 pupils and support school-based literacy development programs.
Keywords: reading comprehension; comprehension strategies; quasi-experimental design; elementary education